The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.athoracsur.2013.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil Is a Superior Vasodilator for the Internal Thoracic Artery in Coronary Surgery

Abstract: Background. Internal thoracic artery (ITA) is a very useful conduit for coronary artery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This method allowed us to evaluate only the local effect of vasodilators on GEA, independent of other grafts and hemodynamic factors. With local application alone, fasudil demonstrates superior vasodilatory effect for internal thoracic artery, 22 radial artery, 16 and GEA, with no hemodynamic changes, no perioperative myocardial infarction, and no vasodilator-related complications. This agent may become the standard vasodilator for arterial graft pretreatment in CABG.…”
Section: Commentmentioning
confidence: 95%
See 1 more Smart Citation
“…This method allowed us to evaluate only the local effect of vasodilators on GEA, independent of other grafts and hemodynamic factors. With local application alone, fasudil demonstrates superior vasodilatory effect for internal thoracic artery, 22 radial artery, 16 and GEA, with no hemodynamic changes, no perioperative myocardial infarction, and no vasodilator-related complications. This agent may become the standard vasodilator for arterial graft pretreatment in CABG.…”
Section: Commentmentioning
confidence: 95%
“…20 In patients with intractable coronary vasospasm after CABG not responding to maximum vasodilatory therapy, fasudil treatment markedly ameliorated the conditions. 21 To apply the potent vasodilatory effect of the Rho kinase inhibitor to CABG, we previously investigated the vasodilatory effect of fasudil on human internal thoracic artery 22 and radial artery grafts 16 and showed the superior vasodilating effect of fasudil over papaverine and VG for both grafts. In the present study, we found that fasudil increased GEA GFF more than threefold, also significantly and markedly more potent than papaverine and VG.…”
Section: Commentmentioning
confidence: 99%
“…After relieving the spasm, it is important to maintain the vessel patency by administering dilators and avoiding constrictors. Here is a list of drugs that cause IMA dilation: sodium nitroprusside [21], organic nitrates [38], calcium channel blockers [4] [52], 17beta-estradiol (evidence only for females) [39], natriuretic peptides [40], low molecular weight heparin [41], alpha-adrenergic blockers (in benign prostate hyperplasia), resveratrol [42], iloprost [43], fasudil [44].…”
Section: Postoperative Managementmentioning
confidence: 99%
“…A more recent study compared the antispastic effect of the commonly used vasodilator, papaverine, with the Rho-kinase inhibitor, fasudil, on free flow following intraluminal injection in the isolated ITA ( 8 ). Fasudil exhibited a very potent vasodilatory effect compared with conventional papaverine.…”
mentioning
confidence: 99%